Pengembangan Buku Ajar pada Mata Kuliah Praktikum Pemesinan Berbasis Project Based Learning - Huda, Khoirul; Iskandar, Ranu; Darsono, Febri Budi; Hidayat, Hanif; Ahda, Zahrah Zakiya (Jurnal Ilmiah Wahana Pendidikan, 2024)
A learning model known as "project-based learning" makes use of projects or activities as media. Project-based learning is used in the lecture-based lathe machining practicum course. development into the creation of a project-based learning-based textbook for student learning materials on lathe machining practicums. The steps of analysis, design, media development, expert validation, and field testing are all included in the textbook development process. The average percentage received from material expert validation was 89%, whereas the average percentage obtained from media expert validation was 90.5%. Following field testing on students participating in a lathe machining practicum and expert validation, the field trial results yielded an 88.66% percentage. Expert validation and field testing results show that the textbook fits into the very good category.